018 Talking to parents about their preferences for their child's place of death: a prospective study. (December 2018) - Henderson, E; Peake, J; Al-Khabbaz, E; Langner, R; Dinsdale, A; Craig, F; Bluebond-Langner, M
Abstract : Background: Government policy identifies home as the preferred place of death (PPOD) for children and young people (CYP) and suggests a home death as an indicator of the quality of care. A recent systematic review found a lack of compelling evidence for both home as the preferred place of death and the suitability of home death as a quality outcome. Rather, one study suggested that offering a discussion is more important for outcomes. Despite these findings, the achievement of preference remains a common quality measure of paediatric palliative care (PPC) services. This study explored factors which influenced the initiation of discussions, preferences, achievement of preferences and their value as an outcome measure. Methods: A prospective case series review was conducted from March 2015-February 2017. Data included: 1) Routinely collected PPC PPOD data for CYP and their parents including the offer of a discussion, preferences expressed and if preference was achieved 2) Field notes taken at multidisciplinary team (MDT) meetings between clinicians where preference was discussed after the child's death 3) Advanced care planning and place of care data extracted from medical notes. Results: Data was available for 256 CYP (117 female). 29% of CYP had a solid tumour malignancy, 10% had a haematological malignancy and 61% died of non-malignant disease. Parents of CYP with malignancies were more likely to be offered a discussion of PPOD (60/73 compared to 84/156 of those with non-malignant disease). A hospital was preferred by 38%, home 28% and hospice 18%. Preference for hospital or hospice was more likely to be achieved. Per clinician report, parent preference was influenced by patient condition, continuity of care, family and social factors and availability of services. Conclusion: Contrary to government policy and voluntary sector statements home deaths are not preferred by most parents. Achievement of PPOD is unsuitable as a measure of service performance.